2016
DOI: 10.1016/j.matdes.2015.09.130
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of aluminum matrix composites reinforced with nano- to micrometer-sized SiC particles

Abstract: ab s t r a c tIn this study, the hot extrusion process was applied to stir cast aluminum matrix-SiC composites in order to im-prove their microstructure and reduce cast part defects. SiC particles were ball milled with Cr, Cu, and Ti as three forms of carrier agents to improve SiC incorporation. Large brittle ceramic particles (average particle size: 80 μm) were fragmented during ball-milling to form nanoparticles in order to reduce the cost of composite manufactur-ing. The experimental results indicate that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(31 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…It has been shown in [14] that the optimal size of titanium diboride particles is from 1 to 5 µm for their use as inoculants in aluminum alloys upon conventional cooling rates and corresponding levels of melt undercooling. At the same time, it is known that for dispersion hardening of aluminum alloys, involving the Orowan mechanism, it is necessary to use particles with size less than 500 nm, such as aluminum oxide [15,16], silicon carbide [17], etc. These fine non-metallic particles become an obstacle for the moving dislocations in aluminum upon its deformation [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in [14] that the optimal size of titanium diboride particles is from 1 to 5 µm for their use as inoculants in aluminum alloys upon conventional cooling rates and corresponding levels of melt undercooling. At the same time, it is known that for dispersion hardening of aluminum alloys, involving the Orowan mechanism, it is necessary to use particles with size less than 500 nm, such as aluminum oxide [15,16], silicon carbide [17], etc. These fine non-metallic particles become an obstacle for the moving dislocations in aluminum upon its deformation [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that SiCp/Al composites usually require secondary deformation, such as forging and hot rolling, before being employed in the industrial field because the properties of the composites can be significantly improved by hot deformation. In recent years, many scholars have performed numerous studies on the hot deformation behavior of a number of alloys and composites and developed corresponding constitutive equations [12][13][14][15][16][17]. For instance, Chen et al [12] constructed a constitutive equation for hybrid particle-reinforced aluminum matrix composites and found an activation energy of the composites of 269 kJ/mol.…”
Section: Introductionmentioning
confidence: 99%
“…SiC particulates are among the most used reinforcements to strengthen the aluminum matrix [9][10][11]. Nonetheless, the great degradation of some properties, such as ductility, in aluminum MMCs reinforced with SiC microparticles is a key challenge [12][13][14]. Tjong reported that the tendency of large ceramic particulates to be cracked during mechanical loading can result in lower ductility and premature failure [15].…”
Section: Introductionmentioning
confidence: 99%